Developing countries in the WTO services negotiations - Juan A. Marchetti (World Trade Organization (WTO), 2004)
The aim of this paper is to analyse developing countries' participation so far in the current round of services negotiations under the Doha Development Agenda. The paper analyses developing countries' negotiating positions, as evidenced by their multilateral negotiating proposals; their initial offers; and, to the extent allowed by the incomplete and sketchy information available, their participation in bilateral market access negotiations. A number of basic themes are raised: the essential role of services for economic development; the high costs imposed by trade protection; the benefits of liberalization; the need to make use of the WTO forum to enhance credibility and sustain domestic regulatory reform programmes; the challenges of regulatory reform and the importance of appropriate sequencing; and the benefits arising from seeking further market access overseas in those areas where developing countries have a comparative advantage.
Keywords: D78; F10; F13; 330; GATS; trade in services; developing countries; liberalization; domestic policy reform